PEMBUATAN GLUKOSA DAN ALKOHOL DARI SAGU (Metroxylon spp.) - Tjutju Nurhayati Syahri; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A study for production of glucose and alcohol from sago (Metroxylon Spp) was conducted on a laboratory scale in the Forest Product Research and Development Centre, Bogor.Treatment condition given for hydrolysis of sago in order to produce glucose was three levels of sulfuric acid (of 0.5 N; 0,75 N and 1.0 N) with three levels of temperature and pressure (of 250°F/15psi, 259°F/20psi, and 274oF/30psi).The reaction time for hydrolysis at each treatment combination were three levels (of 90 minutes, 120 minutes and 150 minutes). Glucose obtained from sago hydrolysis in this experiment was then fermented for producing alcohol by means of Sacharomyses cereuiciae enzym activity from yeast.The result showed that glucose yield during these experiment ranged from 42.8 to 77,6 percent. The maximum glucose yield is obtained from the 274°F/30psi treating condition and sulfuric acid concentration of 1.0 N within 120 minutes of hydrolysis time. Until 120 minutes of hydrolysis period the glucose yield tend to increase with the increasing treatment combination level. The results of glucose tends to decrease afterwards at hydrolysis period of 1.50 minutes.The highest alcohol yield is 14.2 percent and is obtained from fermentation of highest glucose yield of 77.6 percent. Based on the result of chromatographic analysis of alcohol revealed that alcohol produced is classified cu. ethanol (C2H50H)